THE PRANATA MANGSA IN THE PERSPECTIVE OF AN ETHNOSCIENCE APPROACH AS NATURAL SCIENCE TEACHING MATERIALS IN ELEMENTARY SCHOOLS - Habibillah, Nanda Kholifatu Nur; Winarto, Winarto; Wicaksono, Anggit Grahito (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
Javanese people have a close attachment to nature and the environment. One of the local wisdom related to nature that is still used by the Javanese is the pranata mangsa. The pranata mangsa is an indigenous science which can be seen through the perspective of the ethnoscience approach. This research aims (1) to examine the pranata mangsa from the perspective of an ethnoscience approach and (2) to examine the use of the pranata mangsa as teaching materials for science in elementary schools. This research uses a qualitative approach that is library research. Data collection techniques using documentation. The analysis technique used is descriptive qualitative. The results of this research indicate that (1) the pranata mangsa in the perspective of ethnoscience approach is a Javanese calendar system that can combine events between sky and earth by revealing the behavior of flora and fauna in Java and soil characteristics that are affected by temperature changes and (2) the use of the pranata mangsa as a science teaching material in elementary schools can be a learning innovation based on local wisdom that can provide knowledge to students about the phenomena and symptoms of science in a contextual and modern manner related to environmental management, natural resource conservation, environmental pollution, and ecosystems. Keywords: Ethnoscience, Local Wisdom, Natural Science Teaching Materials, Pranata Mangsa